2018
DOI: 10.1363/44e6818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interventions Addressing School Environments or Educational Assets on Adolescent Sexual Health: Systematic Review and Meta-analysis

Abstract: School-based interventions that aim to modify sexual health knowledge, attitudes and behaviors have mixed and often unsustained effects on adolescent sexual health outcomes. However, observational evidence suggests that broader school-related factors, such as school climate and academic attainment, can influence outcomes. METHODS: Nine databases were searched in July 2017 for randomized and quasi-experimental evaluations of interventions addressing school-level environment or student-level educational assets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The prevalence of HIV in this cohort (about 5%) reflects gaps in preventive services and care needs in KwaZulu-Natal and Mpumalanga. Our incidence and prevalence results from the biomarkers are comparable to results from high-school students in rural KwaZulu-Natal undertaken by Abdool Karim and colleagues [ 27 ]. In their sample of female students with a mean age of 16 years, HIV prevalence was 6.4% and HSV-2 prevalence was 10.7%.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of HIV in this cohort (about 5%) reflects gaps in preventive services and care needs in KwaZulu-Natal and Mpumalanga. Our incidence and prevalence results from the biomarkers are comparable to results from high-school students in rural KwaZulu-Natal undertaken by Abdool Karim and colleagues [ 27 ]. In their sample of female students with a mean age of 16 years, HIV prevalence was 6.4% and HSV-2 prevalence was 10.7%.…”
Section: Discussionsupporting
confidence: 86%
“…Reviews of best practice in school sex education have highlighted the importance of a life-skills approach (for example, focusing on decision-making and risk assessment) phased in an age-appropriate way and embedded in a whole-school perspective (Pound et al, 2017). Findings on the impact of specific programmes (either within or outside school) to delay sexual activity and/or reduce risky behaviours have, however, been mixed (Jackson et al, 2012a;Peterson et al, 2019;Lopez et al, 2016aLopez et al, , 2016b. In the UK, a study found that young people who had discussed emergency contraception in school or had been taught about local family planning were more likely to have used contraception at first intercourse.…”
Section: International Researchmentioning
confidence: 99%
“…The results of previous studies also show that a good school climate protects students from premature sexual activity, reduces the risk of unwanted pregnancy and sexually transmitted diseases [26]. A safe climate at school is probably conducive to conversations on any topic, also related to sex education in a broad sense, including the topic of sexual abuse.…”
Section: Discussionmentioning
confidence: 92%
“…The analyzes in this text concern student -with dating experience (n=993) (57.2% of girls and 66.5% of boys). A statistical power analysis was performed for sample size estimation, based on data from a previously published random-effects meta-analysis of 23 studies about school-based interventions aimed to prevent violence and negative attitudes in teen dating relationships [26].…”
Section: Participantsmentioning
confidence: 99%